2011
DOI: 10.1242/dmm.004150
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish deficient for Muscleblind-like 2 exhibit features of myotonic dystrophy

Abstract: SUMMARYMyotonic dystrophy (DM; also known as dystrophia myotonica) is an autosomal dominant disorder that affects the heart, eyes, brain and endocrine system, but the predominant symptoms are neuromuscular, with progressive muscle weakness and wasting. DM presents in two forms, DM1 and DM2, both of which are caused by nucleotide repeat expansions: CTG in the DMPK gene for DM1 and CCTG in ZNF9 (CNBP) for DM2. Previous studies have shown that the mutant mRNAs containing the transcribed CUG or CCUG repeats are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Consistent with what has been reported in nematodes (Norris et al, 2017), zebrafish (Machuca-Tzili et al, 2011) and chickens (Huang et al, 2008), we demonstrated cell-typespecific expression of mbl. Mbl was present in all cells tested that express Dscam2.10B and absent from Dscam2.10A cells.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with what has been reported in nematodes (Norris et al, 2017), zebrafish (Machuca-Tzili et al, 2011) and chickens (Huang et al, 2008), we demonstrated cell-typespecific expression of mbl. Mbl was present in all cells tested that express Dscam2.10B and absent from Dscam2.10A cells.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, this DM1 mouse model exhibited severe muscle wasting, which has not been reported previously in models in which MBNL1 depletion was the main feature (Orengo et al, 2008). More recently, Machuca-Tzili et al generated an mbnl2 knockdown zebrafish model, which exhibits features of DM (Machuca-Tzili et al, 2011). They showed that loss of zebrafish mbnl2 function causes muscle defects and splicing abnormalities of clcn1 and tnnt2 transcripts, similar to those observed in DM1 patients (Machuca-Tzili et al, 2011).…”
Section: Muscleblind (Mbnl) Family Proteinssupporting
confidence: 50%
“…Evolutionary conservation of muscle-enriched alternative splicing events has also been reported by others(Bland et al, 2010), with Rbfox proteins implicated as critical regulators along with members of the MBNL and CELF families of splicing factors. Disruption of splicing networks mediated by the latter factors is a hallmark of myotonic dystrophy(Cooper et al, 2009; Du et al, 2010) and zebrafish MBNL2 morphants also exhibit splicing defects and features of myotonic dystrophy (Machuca-Tzili et al, 2011). Mouse knockout experiments have implicated additional splicing factors such as SF2/ASF (SFRS1) and SC35 (SFRS2) as important contributors to alternative splicing in muscle (Ding et al, 2004; Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%